Penal modernism: an American tragedy - Farmer, Lindsay (2014)
This paper discusses Whitman’s analysis of penal modernism. While I am in agreement with the central claim that penal modernism has been ignored and caricatured, I argue here that Whitman’s account of the penal modernist theory of judging must be understood in the context of a wider reframing of the social functions of the criminal law in penal modernism. This is explored by considering the unusual connection that the novel An American Tragedy (1925) has to the history of American criminal law, and the light that this can shed on the question of the meaning of penal modernism